Comparison of Different Volume Reactor for Batik Wastewater Pre-Treatment with Ozonation to Improve Biodegradability - Sofiyah, Evi Siti; Septiariva, Iva Yenis; Helmy, Qomarudin; Notodarmojo, Suprihanto; Suryawan, I Wayan Koko (Reaktor, 2022)
Batik is a unique ethnic and heritage textile from Indonesia with low biodegradability (BOD5/COD) and demanding biological wastewater treatment. However, in its application a high biodegradability value is needed. To increase biodegradability the ozonation process can be used as pre-treatment. The purpose of this study is to determine the effectiveness of ozone pre-treatment in color removal, COD removal, and changes in biodegradability. This study was divided into two types of the reactor with a volume of 2 L and 16 L with each dose of 4 mg/min and 40 mg/min. The results of color removal in the reactor with a volume of 2 L showed a value of 85% for color removal and 34.6% for COD removal. The reduction in efficiency occurred in the color removal to 65% in reactor 16 L. The removal of COD with a volume of 16 L was not evenly distributed at each altitude of 43; 35; and 33% (50; 100; 150 cm). Biodegradability increased from 0.143 to 0,49 (2L reactor) and 0.4-0.45 (16L reactor), this allows for the application of higher biological wastewater treatment. Which the NH3-N and total phenol removal efficiencies of 12.9%-31.4% and 3-21.2%, respectively.